Initial Identification of Zakat Management Applications - Abdullah Mubarok; Efri Bahri (Yayasan Mitra Peduli Indonesia, 2025)
The use of zakat management applications supports the success of zakat management in Indonesia. This study aims to identify zakat management applications in Indonesia. This study employs a qualitative method with a descriptive approach, incorporating a literature review. Data is sourced from journal article databases, the Google Play Store, the App Store, websites/applications, and the Google Scholar search engine. Inclusion criteria are active applications that support zakat management. Analysis is conducted based on content that aligns with the research theme, specifically the keyword 'zakat application'. The results show that there are three main groups of actors managing zakat applications in Indonesia: BAZNAS, the Zakat Amil Institution (LAZ), and Fintech (financial technology) platforms. Zakat management authorities in Indonesia need to provide support and protection for zakat management applications to minimize risks, maintain the trust of muzaki (those who pay zakat), and deliver the best service to mustahiq (those who receive zakat).